2020
DOI: 10.3390/ijerph17020601
|View full text |Cite
|
Sign up to set email alerts
|

(Un)bounded Social Work?—Analysis of Working Conditions in Refugee and Homeless Aid in Relation to Perceived Job Stress and Job Satisfaction

Abstract: Little is known about working conditions of social workers providing help in homeless and refugee aid. Therefore, the present study examined their work-related demands, job and personal resources as well as workplace violence, domain-specific demands, and gender-related differences. Job demands and resources were analyzed with regard to their association with job stress and job satisfaction. Two hundred and fifty-three social workers (69.2% female, 30.8% male) from four federal states in Germany (Berlin, Hambu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 44 publications
1
10
1
Order By: Relevance
“…Adverse to postulated hypotheses and results of previous studies,55–59 present findings indicated that resilience was neither associated with burn-out symptoms nor with work engagement. However, correlation analysis was in line with our hypothesis highlighting significant associations to work engagement and burn-out symptoms.…”
Section: Discussioncontrasting
confidence: 91%
See 2 more Smart Citations
“…Adverse to postulated hypotheses and results of previous studies,55–59 present findings indicated that resilience was neither associated with burn-out symptoms nor with work engagement. However, correlation analysis was in line with our hypothesis highlighting significant associations to work engagement and burn-out symptoms.…”
Section: Discussioncontrasting
confidence: 91%
“…52 Those differences were also apparent when comparing means of supervisors regarding their influence at work (M=71.81) to other occupations (M=42). 75 Personal resources in relation to burn-out symptoms and work engagement Adverse to postulated hypotheses and results of previous studies, [55][56][57][58][59] present findings indicated that resilience was neither associated with burn-out symptoms nor with work engagement. However, correlation analysis was in line with our hypothesis highlighting significant associations to work engagement and burn-out symptoms.…”
Section: Open Accessmentioning
confidence: 54%
See 1 more Smart Citation
“…For example, Mucci [ 5 ] observed that working conditions such as high work demands, job control, type of leadership, peer support, company organization, and even gender (higher among women than among men) correlated with WV. Following the same line of research, but focusing on individual factors, Robelski [ 6 ] showed that emotional demands, job satisfaction, and each person’s own resilience had a direct influence on WV. On the other hand, the consequences generated by violence at work are related to the high levels of stress experienced.…”
Section: Introductionmentioning
confidence: 99%
“…10.29252/johe. 9.3.180 Stress is one of the factors exerting destructive physical and psychological effects [3]. Besides, OS is recognized as one of the most effective factors in maintaining physical and mental health among employees [4].…”
Section: Introductionmentioning
confidence: 99%